Airplane Analytic-geometric modeling - Павлова, С.В.; Оснач, С.Г. (Proceedings of National Aviation University (archive), 2005)
Analytic-computer airplane designing method is given. This method allows uses to predict airplane aerodynamic characteristics due to airplane configuration structure, while designing.